The global epidemiology of preterm birth - Vogel, Joshua P.; Chawanpaiboon, Saifon; Moller, Ann-Beth; Watananirun, Kanokwaroon; Bonet, Mercedes; Lumbiganon, Pisake (Best practice & research. Clinical obstetrics & gynaecology, 2018)
This article is a part of a series that focuses on the current state of evidence and practice related to preterm birth prevention. We provide an overview of current knowledge (and limitations) on the global epidemiology of preterm birth, particularly around how preterm birth is defined, measured, and classified, and what is known regarding its risk factors, causes, and outcomes. Despite the reported associations between preterm birth and a wide range of socio-demographic, medical, obstetric, fetal, and environmental factors, approximately two-thirds of preterm births occur without an evident risk factor. Efforts to standardize definitions and compare preterm birth rates internationally have yielded important insights into the epidemiology of preterm birth and how it could be prevented. •Preterm birth affects approximately 11% of births worldwide. However, estimation is complicated by differences in measurement of gestational age, preterm definitions, as well as differences in data collection and reporting.•Although many factors have been shown to increase the risk of spontaneous preterm birth, the majority of preterm births occur in women without a clear risk factor.•Long-term studies have shown that the deleterious effects of preterm birth continue to affect health and welfare in adult life.•Addressing preterm birth is critical to addressing neonatal and child mortality and morbidity, particularly in resource-poor settings.